A Review of Research in Translation Technology Based on Citespace - Ding Lijie (International Journal of Education and Humanities, 2024)
To explore the research hotspots and trends in translation technology, this study utilizes the literature visualization analysis software CiteSpace to conduct a bibliometric analysis of relevant literature on translation technology from 2013 to 2023 in the Web of Science and China National Knowledge Infrastructure. This research indicates a continuous increase in annual publications from the Web of Science, while the publications from China National Knowledge Infrastructure show no clear upward or downward pattern over the past 10 years. This study also reveals that scholars in the field of translation technology mainly publish papers independently. Most importantly, this study discovers that machine translation, translation technology, artificial intelligence, computer-assisted translation, post-translation editing, neural machine translation, and talent training emerge as research hotspots in the field. Post-editing, google translate and natural language processing are the research frontiers in the field of machine translation in the last three years. This study can provide scholars in the field with the latest hotspots and frontiers so that they can conduct more innovative research